2015
DOI: 10.1002/sdtp.10235
|View full text |Cite
|
Sign up to set email alerts
|

43.1: Invited Paper: UB‐FFS: New Materials for Advanced Mobile Applications

Abstract: In the recent years, displays for mobile electronic devices have been revolutionized, mostly driven by smartphones and tablets. Strongest trends are (besides growing sizes) the ever-increasing resolution, improved contrast, very good viewing angle and color performance. This went hand in hand with a trend to more "refined" display technologies, namely fringe field switching (FFS). Now, as the latest step, Ultra-Brightness (UB-) FFS is at the brink to widespread commercialization in mobile and IT displays. It c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…This assumes that the liquid crystal has a fixed boundary in the x ‐direction orthogonal to it just as it has a fixed boundary in the upper and lower substrates. With respect to the conditions where K 11 is twice the value of K 22 37 and the distance equals the liquid crystal layer thickness d , the response time is expressed by τdecaySLCtrueγ1[]K22bold-italicd2+2K22bold-italicd2π2=trueγ1[]3K22d2π2=trueτdecayconventional3. …”
Section: Short‐range Lurch Control In‐plane Switching Modementioning
confidence: 99%
“…This assumes that the liquid crystal has a fixed boundary in the x ‐direction orthogonal to it just as it has a fixed boundary in the upper and lower substrates. With respect to the conditions where K 11 is twice the value of K 22 37 and the distance equals the liquid crystal layer thickness d , the response time is expressed by τdecaySLCtrueγ1[]K22bold-italicd2+2K22bold-italicd2π2=trueγ1[]3K22d2π2=trueτdecayconventional3. …”
Section: Short‐range Lurch Control In‐plane Switching Modementioning
confidence: 99%
“…The response time of a liquid crystal is proportional to γ1/K22. It was found that there is a close relation of the twist elastic constant (K22) and the splay elastic constant (K11) and that K22 can be approximated as about half of K11 [6]. Due to this result it is possible to estimate the response time by γ1/K11 for in-plane switching test cells.…”
Section: Response Time Improvements Of Ubplus Mixture Conceptsmentioning
confidence: 94%
“…Challenges in using a liquid crystal mixture with a negative dielectric anistropy in the past might be based on the higher rotational viscosity (slower switching), lower reliability and lower polarity (higher driving voltages necessary). As a result of continuous development of new liquid crystal materials having a negative dielectric anistropy the drawbacks are becoming less significant [6]. With further developments of new materials UBplus should be able to overcome the last challenges and offer more freedom to the design of future large size, high resolution liquid crystal displays.…”
Section: Figure 1 Development Of Liquid Crystal Mixtures For Improvementioning
confidence: 99%
“…Liquid Crystal Display (LCD) devices have been widely used at automotive display, for instance instrument cluster, center information display [1]. Twisted nematic (TN) [2] mode and Super Fine TFT (SFT) [3][4][5] mode are two popular liquid crystal display modes at Automotive Display. But viewing angle contrast is always serious concern at Automotive Display.…”
Section: Introductionmentioning
confidence: 99%